FESTIVAL KALIPUTIH SEBAGAI WUJUD KOMODIFIKASI BUDAYA DAN PELESTARIAN KEARIFAN LOKAL DI DESA SEMPOR KEBUMEN - Nanda Kusuma Sabiq Mujtaba; Maula Farah Azizah; Fadhia Afrilia Salsabila; Dilla Apriana Yustika Putri; Rahmat Putra Perdana; Misel Fandani; Indra Yunarto; Raihanah Salsabila; Rizky Hidayat; Baiqi Nilma Sabrina Fadilah (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
The Kaliputih Festival in Kaliputih Hamlet, Sempor Village, Kebumen Regency, is a form of cultural commodification that preserves local wisdom values while contributing to the economy and cultural identity of the community. This festival has evolved from a village ritual into a culture- and environment-based tourism event, in line with the growing interest of visitors. This study aims to analyze the process of cultural commodification and examine its impact on the cultural resilience of the local community. The research employs a qualitative method with an ethnographic approach, utilizing participatory observation, interviews, and document studies. The findings reveal that the festival successfully boosts the local economy through various forms of commodification, such as traditional markets, signature souvenirs, and educational tour packages. However, challenges remain in maintaining traditional values, particularly regarding the regeneration of cultural practitioners and the risk of excessive commercialization. Therefore, a sustainability strategy involving the government, communities, and local society is necessary to ensure the festival remains relevant without losing its cultural essence. With proper management, the Kaliputih Festival can serve as an example of how cultural commodification can support both the preservation of traditions and the well-being of the community in a balanced and sustainable manner.